The Dynamic Mu Transpososome: MuB activation prevents disintegration - Lemberg, Kathryn M. (2007)
DNA transposases use a single active center to sequentially cleave the transposable element DNA and join this DNA to a target site. Recombination requires controlled conformational changes within the transposase to ensure that these chemically distinct steps occur at the right time and place, and that the reaction proceeds in the net forward direction. Mu transposition is catalyzed by a stable complex of MuA transposase bound to paired Mu DNA ends (a transpososome). We find that Mu transpososomes efficiently catalyze disintegration when recombination on one end of the Mu DNA is blocked. The MuB activator protein controls the integration vs. disintegration equilibrium. When MuB is present, disintegration occurs slowly and transpososomes that have disintegrated catalyze subsequent rounds of recombination. In the absence of MuB, disintegration goes to completion. These results together with experiments mapping the MuA-MuB contacts during DNA joining suggest that MuB controls progression of recombination by specifically stabilizing a concerted transition to the ‘joining’ configuration of MuA. Thus, we propose that MuB's interaction with the transpososome actively promotes coupled joining of both ends of the element DNA into the same target site and thus may provide a mechanism to antagonize formation of single-end transposition products.